Analysis of Project Budget Plan with Public Private Partnership Through Availability Payment (Case Study: Sumadra-Bungbulang Road, Garut Regency) - Bihaki Ridwan; Pratikso; Rachmat Mudiyono (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2023)
Investing in road infrastructure can stimulate economic growth and provide support for various developments. To ensure success, it is crucial to allocate funds based on technical calculations and specifications. This article focuses on budget planning for the Sumadra-Bungbulang road infrastructure project using the Public-Private Partnership model as a potential solution to achieve infrastructure goals. Budget calculations show a positive NPV and a Payback Period that meets the concession deadline. Additionally, the IRR target of 12% agreed upon by public and private institutions is also achieved. Therefore, the proposal for the road project through Public-Private Partnership is worthy of consideration by the West Java Governor for short-list or long-list selection.